Growth and Production of Amorphophallus paeoniifolius Dennst. Nicolson from Different Corm Weights - Santosa, Edi; Sugiyama, Nobuo (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
The effect of different seed corm weight on the growth and production of elephant foot yams (Amorphophallus paeonifolius Dennst. Nicolson) were studied. Two forms of corm with same weight were prepared, i.e., whole corm and vertically sectioned by 1/2. The fresh mass of each whole corm and corm section was the same. Six different corm weights were compared, i.e., 50, 100, 200, 500, 1000 and 2000 g. Growth and development of elephant foot yam were determined by corm weigth, large seed corm produced larger leaf and fresh mass of daughter corms. On the contrary, number of leaf decreased with increasing seed corm weight. Plants from whole seed corms emerged earlier and they were larger than those from the sectioned corms, irrespective of weight. Plants from small sized whole corm emerged earlier than the larger ones. Dissecting the main bud caused the development of lateral buds, resulted in a delay of leaf emergence. The lower yield obtained by the use of sections might be related to the late emergence leading to shorter vegetative period in the field. In the cultivation, it is recommended to use whole seed corms of 100 or 200 g. Key words : Elephant foot yams, tuber crop, Araceae, corm weight, tuberization rate